PERAN SOCIOPRENEUR PADA LEMBAGA BIMBINGAN BELAJAR GRATIS DI DESA TEMU KABUPATEN SIDOARJO - aditya surya nanda; Fitryani Fitryani (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
The purpose of this PKM-CSR is to provide additional learning for underprivileged students for free and to help educators to create a good, structured and detailed financial governance system. The number of participants in this PKM is 10 elementary school children who are classified as underprivileged. This service is carried out in Temu Village, Sidoarjo Regency.The implementation method carried out is in the form of assistance to partners which is carried out for 2 months as well as basic financial management training to partners. The partner's main problem is the lack of knowledge about reliable social preneur-based HR governance and digitalization. Partners have not been able to use online and social media-based applications. It is hoped that this incentive assistance to partners can help children complete students' tasks in using online-based learning media.